2018
DOI: 10.12968/bjon.2018.27.4.212
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence nurses' assessment of patient acuity and response to acute deterioration

Abstract: Factors that influence nurses' assessment of patient acuity and response to acute deterioration.http://researchonline.ljmu.ac.uk/8425/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their private study or for non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 40 publications
(24 reference statements)
1
44
0
10
Order By: Relevance
“…The nurses also said that they feared that doctors would emphasize measurements at the expense of nurses' observations and clinical judgements. These findings correspond with the findings of a recent study that suggested that when using a tool, nurses relied on the numerical escalation of the system to identify deteriorating patients rather than their own clinical judgement and consequently, the participants found it challenging to escalate care when a score was low (Dalton, Harrison, Malin, & Leavey, 2018).…”
Section: National Early Warning Score and Professional Competencesupporting
confidence: 88%
“…The nurses also said that they feared that doctors would emphasize measurements at the expense of nurses' observations and clinical judgements. These findings correspond with the findings of a recent study that suggested that when using a tool, nurses relied on the numerical escalation of the system to identify deteriorating patients rather than their own clinical judgement and consequently, the participants found it challenging to escalate care when a score was low (Dalton, Harrison, Malin, & Leavey, 2018).…”
Section: National Early Warning Score and Professional Competencesupporting
confidence: 88%
“…Nurses acknowledged that their knowing the patient prompted them to act on their intuition. Intuition or a “gut feeling” has been a common theme in recognising the deterioration of a patient (Cioffi et al, ; Dalton et al, ; Donohue & Endacott, ; McDonnell et al ., 2012), and literature has suggested that nurses resist contacting doctors on intuition alone as they believe they must defend their assumptions (Dalton et al, ; Massey et al, ). This study demonstrated that once nurses were concerned about a patient's condition or acute illness severity, they undertook a patient assessment by completing the EWS and escalated care using their own clinical judgement and were not reliant on the EWS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Compliance and adherence to EWS are influenced by many factors, including nurses’ intuition, doctors’ response times, team collaboration, communication and ward environments (Dalton, Harrison, Malin, & Leavey, ; Odell, ; Petersen, Rasmussen, & Rydahl‐Hansen, ; Smith & Aitken, ). Moreover, weekends and nights have been identified as periods of non‐adherence in recording the EWS due to reduced staffing levels and nurses not wishing to disturb sleeping patients (Gordon & Beckett, ; Hands et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in most instances, HCPs described relying on intuition and feeling a sense of concern to pinpoint signs of decline. Intuition is fundamental in clinical nursing (Dalton, Harrison, Malin, & Leavey, 2018), though clinical decision‐making is complex, and the process of clinical judgement involves more aspects (Tanner, 2006). The results indicated differences when a patient's situation was vague or critical.…”
Section: Discussionmentioning
confidence: 99%